IMPACT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND LEADERSHIP STYLE (PATH GOAL THEORY) ON WORK PRODUCTIVITY IN PHARMACEUTICAL COMPANIES IN BANDUNG CITY - Shendy Amalia; Abdul Salam; Dede Otong; Reza Aditya Wibowo; BagasPahlawan Yudapraja (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Declining level of work productivity of employees in a company or organization is a symptom or emergence of problems that can cause companies to run poorly or unstable because company targets that are not reached. This study aims to see how much influence Organizational Citizenship Behavior (OCB) and Leadership Style (Path Goal Theory) on Employee Productivity in Pharmaceutical companies in the city of Bandung. The population and sample of 50 people using saturated sampling techniques in the domestic sales division, namely in the private sales division. This research method uses multiple regression. The results of this study indicate that Organizational Citizenship Behavior (OCB) partially has a significant effect on Productivity Performance. As for the variable leadership style (path goal theory) does not have a significant effect on employee productivity. For simultaneous or joint test has a significant effect on employee productivity, with a 94% influence.